2007
DOI: 10.1111/j.1600-0501.2007.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel bone scraper for intraoral harvesting: a device for filling small bone defects

Abstract: In conclusion, Safescraper is capable of collecting adequate amounts of cortical bone chips from different intraoral sites. The procedure is effective for treating alveolar defects for endosseous implant insertion and provides good healing of small bone defects after grafting with bone chips. The study indicates that Safescraper is a very useful device for in-office bone harvesting procedures in routine peri-implant bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
1
24
1
2
Order By: Relevance
“…Thin sections were stained with toluidine blue or trichrome Gomori stain. 29 The microradiographs and the sections were analyzed and photographed using a microscope (Axiophot; Carl Zeiss AG, Oberkochen, Germany) under ordinary light.…”
Section: Histologic Preparationmentioning
confidence: 99%
“…Thin sections were stained with toluidine blue or trichrome Gomori stain. 29 The microradiographs and the sections were analyzed and photographed using a microscope (Axiophot; Carl Zeiss AG, Oberkochen, Germany) under ordinary light.…”
Section: Histologic Preparationmentioning
confidence: 99%
“…10 Moreover, it has been reported that early stages of bone regeneration are positively influenced by autogenous bone grafts with a smaller particle size, such as that obtained with low-speed drilling. 24 In conclusion, many useful procedures are available for harvesting particulate bone to fill small bone defects, fenestrations, and dehiscences associated with dental implants. The 3 methods examined in the present study are easy to apply, but certain precautions must be taken to avoid infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean CFU/g of bone debris collected by the bone scraper was higher as compared to the bone chisel and trephine drill. Since a similar device was also reported as a useful instrument for intraoral bone graft [12], we compared the bacteria levels of bone debris collected by another bone scraper similar to the device used in this study, with nearly the same level found in bone debris collected by both devices (data not shown). Direct trapping of salivary fluid into the chamber by large movements of this instrument along the bone surface may be related to the high levels of bacterial contamination.…”
Section: Discussionmentioning
confidence: 99%